High‐level language competencies and Theory of Mind in a group of children with Klinefelter syndrome. Issue 2 (8th January 2019) - Melogno, Sergio; Pinto, M. Antonietta; Badolato, Fausto; Sist, Eleonora; Esposito, Antonella; Orsolini, Margherita; Tarani, Luigi
Abstract : Klinefelter syndrome (KS) is a genetic anomaly involving the presence of one or more supernumerary X chromosomes in male individuals. In the cognitive profile of these individuals, strengths are found in nonverbal abilities, whereas weaknesses are observed in executive function, language, and academic performance. Our study is based on a comparison between eight children diagnosed with KS (47, XXY) (age range: 9–13 years; IQ range: 80–123), with no delay in language development, and eight typically developing (TD) controls. We explored a range of high‐level language competencies and Theory of Mind (ToM) in addition to basic language competency. High‐level language competencies were assessed by a battery that measures pragmatic language skills and a metaphor comprehension test (MCT). To assess ToM, we administered the corresponding subtest of the NEPSY II. Basic language competence was assessed by the NEPSY II Comprehension of Instructions subtest. Although basic language performance did not differentiate the individuals with KS from the TD controls, relevant differences appeared in some of the high‐level language competencies as well as in the ToM task. All tasks in which the individuals with KS performed less well were characterized by complex inferential processes. Some possible clinical and educational implications are discussed.